Trends and disparities in health status and health care in the United States during COVID-19 pandemic - Zhiyuan Wu; Frank Qian; Siyu Zou; Xinye Zou; Ruolin Zhang; Xiuhua Guo; Haibin Li (BMC Medicine)
Abstract Background Concerns exist over a possible worsening of disparities in health status and health care access across racial/ethnic and income groups during the COVID-19 pandemic. We aimed to characterize trends in racial/ethnic and income differences in self-reported measures of health status and health care access among US adults. Methods This serial cross-sectional nationally representative study included adults (age ≥ 18 years) participating in the National Health Interview Survey (NHIS) from 2019 to 2022. Self-reported health status (poor or fair health status, functional limitation, clinician-diagnosed depression or anxiety disorders) and health care access and affordability were collected. Results Our analysis included 107,230 adults (mean [SE] age, 48.1 [0.1] years, 51.6% women), of whom 6.1% were Asian, 12.1% were Black, 17.3% were Latino/Hispanic, and 64.5% were White. Black individuals with low income had the highest prevalence of poor or fair health status (30.9% [95% CI, 27.8%–34.3%] in 2019 and 28.4% [95% CI, 25.1% to 32.0%] in 2022), and these racial/ethnic gaps did not change significantly, irrespective of income levels. The prevalence of clinician-diagnosed depression or anxiety disorders increased from 2019 to 2022 for all racial/ethnic groups, especially for Whites (from 32.6% [95% CI, 30.8%–34.4%] to 38.2% [95% CI, 36.4% to 40.1%], P < 0.001). There was no significant change in functional limitations during the pandemic. Latino/Hispanic individuals with low income had the highest estimated prevalence of limited health care access from 2019 to 2022. Health insurance access and affordability significantly improved for White individuals with low income from 2019 to 2022 (P < 0.001), but not for other racial/ethnic groups. Racial/ethnic gaps in health care access and affordability did not change significantly, irrespective of income levels. Conclusions In a serial cross-sectional survey study of US adults during the COVID-19 pandemic, prevalence of clinician-diagnosed depression or anxiety disorders significantly increased. Racial and ethnic differences in health status and health care access either persisted or widened over time.